Reading Material-Based Content Analysis in Senior High School English Textbooks in Indonesia - Cicih Nuraeni; Didi Sukyadi; Fazri Nur Yusuf (Metathesis: Journal of English Language, Literature, and Teaching, 2023)
English textbooks play a vital role in providing students with language learning input in class activities. Unfortunately, the selection and evaluation of English textbooks has often received insufficient attention and thought. Content such as reading material receives less attention than layout analysis, design, and cultural understanding. The purpose of this study is to investigate the extent to which reading material cover the genres and skills presented in senior high school English textbooks in Indonesia. The qualitative-based content analysis method was used in this study. There were three English textbooks observed, namely those for grades 10, 11, and 12 published by Ministry of Education and Culture in Indonesia. The aspects observed in reading materials include reading genres and skills based on Brown's theory. The study discovered textbooks are dominated by personal reading with 17 reading material and 14 academic materials. Meanwhile, job-related reading is limited to class 10 textbooks. When it comes to reading skills, macroskills take precedence over microskills. Furthermore, based on these findings it can be concluded that the textbooks need to be developed to provide a balanced portion of reading genres and skills in each chapter. The limitations and suggestions are further discussed.